(untitled) (International Journal of Biomedical Research, 2014)
Introduction: Relapse cases of pulmonary tuberculosis (PTB) and drug resistance is increasing in National Tuberculosis Centre (NTC), National Tuberculosis Control Programme, Nepal (NTP) and the predictors of relapse PTB is multi-factorial. Initial drug resistant was found to be associated with high relapse cases, so public awareness for regularity of drug intake is highly recommended. Age, sex, occupation, smoking, alcoholism may be important risk factor for relapse. The study aims to determine the prevalence, anti-tubercular drug resistance and predictors of relapse pulmpnary tuberculosis (PTB) cases. Materials and methods: Suspected relapse PTB patients were enrolled and microscopy, culture and drug susceptibility testing were done for all culture positive cases. Result and conclusion: Prevalence of relapse PTB was 45.5% (n=127). M. tuberculosis isolates resistant to at least one anti-TB drug were 25.4% (n=31), 35.5% (n=11) were mono resistant and 64.5% (n=20) were poly resistant. Multi-drug resistance were 14% (n=17). The farmer (OR=1.96), who rest at home (OR=1.12), smokers (OR=1.48), alcoholics (OR=1.73) and those who were on irregular drugs (OR=4.10) were at high risk of relapse PTB. Almost half of patients studied had relapse PTB and drug resistance was noteworthy. Close monitoring and follow up, adherence of treatment and risk factors identified should be addressed to reduce relapses and emergence of drug resistance.